Endoscopic Detachable Snare Ligation Therapy for Colonic Diverticular Hemorrhage Improves Procedure Time Compared to Endoscopic Band Ligation - Hamada, Koichi; Kawano, Koichiro; Nishida, Shinya; Shiwa, Yoshiki; Horikawa, Yoshinori; Techigawara, Kae; Fukushima, Daizo; Noriyuki, Nishino; Honda, Michitaka (Turkish Journal of Gastroenterology, 2022)
Background: The clipping method is widely used in endoscopic hemostasis for colonic diverticular hemorrhage. Recently, rebleeding was shown to be less common in ligation therapy than in clipping. Ligation methods include endoscopic band ligation (EBL) and endoscopic detachable snare ligation (EDSL). No studies have compared procedure times for EBL and EDSL. The present study aimed to compare EDSL and EBL in terms of procedure time.Methods: In this single-center retrospective observational cohort study, we evaluated the data of 39 patients who underwent EBL or EDSL for colonic diverticular hemorrhage. The primary and secondary outcomes measured were the total procedure time and early rebleeding rate, respectively.Results: Among the 39 patients included in the study, 18 underwent EBL, and 21 underwent EDSL for hemostasis. The median total pro- cedure times for the EBL and EDSL groups were 50 (range, 30-80) minutes and 35 (range, 18-55) minutes, respectively, demonstrating that the total colonoscopy time was significantly shorter in the EDSL group (P < .001). The early rebleeding rate was 11.1% (2/18) in the EBL group and 4.8% (1/21) in the EDSL group (P = .246).Conclusion: Important improvements in procedure time were achieved in the EDSL group. Based on our results, we believe that EDSL may reduce patient and endoscopist burden.